Highly Efficient PANI-WH Novel Composite for Remediation of Ni(II), Pb(II), and Cu(II) From Wastewater - Arsalan, Muhammad; Siddique, Imran; Awais, Azka; Baoji, Miao; Khan, Ilyas; Badran, Mohamed; Mousa, Abd Allah A. (Frontiers in Environmental Science, 2022)
: The current study comprises the synthesis of a novel composite Polyaniline-Wheat Husk (PANI-WH), and the adsorption of heavy metals (Cu, Pb, Ni) by using this composite. Characterization like SEM, XRD, XPS and FT-IR of the composite were used to check the chemical structure and morphology of the novel composite before and after the adsorption of heavy metals. The results indicate that adsorption performance of PANI-WH novel composite (on heavy metals) are good with excellent binding capacity of 155 mg g-1 for Ni, 95 mg g-1 and 110 mg g-1 for Cu and Pb respectively. The PANI-WH novel composite show maximum adsorption at optimum conditions. The remediation capacity of heavy metals was observed up to 99% by using PANI-WH composite. The present study also involves kinetic, thermodynamics and isotherm studies, showing that adsorption of heavy metals is increased by using PANI-WH composite. The material used in this work come from industrial/agricultural by products which provide a twofold benefit of not only providing a means of treating water but also an effective method of utilization of these by product which otherwise form an additional waste stream. The PANI-WH show good stability and reusability. In future PANI-WH composite can be used for the detection of other heavy metals.